(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: This study aims to evaluate the prevalence of the scores of USPHS guidelines for marginal adaptation and check its association with the qualification of the dental students.Materials and Methods: This retrospective study was carried out from the data obtained from the patients’ case sheet. A total of 730 subjects were selected, undergoing treatment for fixed dental prosthesis. The prevalence of three different scores was checked. Group 1- Score of 0, Group 2- Score of 1, Group 3-Score of 2. The frequency of each score was checked and a Chi square test was done to evaluate the correlation between the scores and qualification of the dental student.Results: It was observed that maximum students achieved a score of 0, followed by a score of 1 and very few people achieved a score of 2. Within the groups, it was seen that the prevalence of the score 0 was seen more in undergraduate students as compared to the post graduate students.Conclusion: It can be concluded that the overall results achieved by the students were good. Further studies need to be done to verify the results.Clinical Significance: Marginal fit of the prosthesis is one of the major factors influencing the strength and longevity of the prosthesis. Marginal discrepancies can lead to a lot of endodontic and periodontal problems. Hence, the clinician should try and achieve a good marginal adaptation.